Prevalence of sacrococcygeal pilonidal disease in Turkey - Duman, Kazim; Girgin, Mustafa; Harlak, Ali (Elsevier Singapore Pte Ltd, 2017)
Background: Pilonidal sinus disease is frequently observed in the producing population; despite it not being a malignant disease, attention of clinicians to this disease has increased. Studies on this disease have not clearly revealed its prevalence. We aimed to detect its dispersion characteristics in our country. Materials and methods: Our study was designed as a descriptive study involving a large number of patients. A total of 19,013 candidates, aged between 17 years and 28 years and coming from different regions of the country, who applied to be students or officials of the state's schools and institutions, were enrolled in the study. Examination was performed including the perineal region, the presence of any comorbid diseases was noted, and clinical types of pilonidal sinus disease were detected according to Tezel's classification and recorded. Results: Pilonidal sinus was detected in a total of 1258 (6.6%) candidates, of whom 72 (0.37%) were female and 1186 (6.23%) male. Our clinical experience showed that pilonidal cysts had a higher incidence in the Turkish population than in other populations, and it was especially increased in individuals of military age. Conclusion: We believe that soldiers coming from different regions of Turkey and candidates applying for auxiliary staff positions provide a small sample group resembling a representation of the whole of Turkey. (C) 2016 Asian Surgical Association and Taiwan Robotic Surgical Association. Publishing services by Elsevier B.V.
Keywords: dispersion characteristics; pilonidal sinus disease; Turkish population